20 Years of the MENC Biennial Conference: A Content Analysis. (April 2016) - Palkki, Joshua; Albert, Daniel J.; Hill, Stuart Chapman; Shaw, Ryan D.
The purpose of this study was to investigate the content and intended audiences for educational sessions offered at MENC biennial conferences in order to illuminate trends and topics in professional development. The researchers performed a content analysis of each session ( N = 2, 593) using program booklets from conferences between 1988 and 2008, creating a coding scheme with separate codes for audience focus and session content. After establishing sufficient interjudge agreement, the researchers coded all educational sessions offered at the conferences from 1988 to 2008. Results indicated that the number of sessions targeted at specific audiences (e.g., choral teachers only) remained small relative to those targeting broader audiences. Content coding revealed large increases in the number of sessions focused on technology and a slight decrease in the number of sessions focused on traditional large ensembles. Session content sometimes followed professional trends (e.g., the inception of the National Standards in 1994) but did not reflect increased attention in the profession to topics such as creativity and students with exceptionalities. These findings have important implications for those planning state and national music education conferences and for music educators who attend these professional development events.